2019
DOI: 10.1063/1.5085881
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell and platelet diffusivity and margination in the presence of cross-stream gradients in blood flows

Abstract: The radial distribution of cells in blood flow inside vessels is highly non-homogeneous. This leads to numerous important properties of blood, yet the mechanisms shaping these distributions are not fully understood. The motion of cells is governed by a variety of hydrodynamic interactions and cell-deformation mechanics. Properties, such as the effective cell diffusivity, are therefore difficult to investigate in flows other than pure shear flows. In this work, several single-cell, cell-pair, and large-scale ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 75 publications
4
38
1
Order By: Relevance
“…The diffusion coefficients were computed per radius region and averaged over 0.4 seconds, with a time window of 0.5ms. We follow the specific procedure from a previous study [33] and confirm that RBC radial diffusion increases from the center of the pipe towards the wall, following the increase of shear rate. Radial diffusivities are shown in the left panels of PLOS COMPUTATIONAL BIOLOGY simulations, an increase of RBC D rr in all regions of the pipe is observed.…”
Section: Bulk Rheology Including Stiff Red Blood Cellsmentioning
confidence: 69%
See 3 more Smart Citations
“…The diffusion coefficients were computed per radius region and averaged over 0.4 seconds, with a time window of 0.5ms. We follow the specific procedure from a previous study [33] and confirm that RBC radial diffusion increases from the center of the pipe towards the wall, following the increase of shear rate. Radial diffusivities are shown in the left panels of PLOS COMPUTATIONAL BIOLOGY simulations, an increase of RBC D rr in all regions of the pipe is observed.…”
Section: Bulk Rheology Including Stiff Red Blood Cellsmentioning
confidence: 69%
“…HemoCell has been validated to reproduce the mechanical responses of an individual, healthy, RBC induced by sheared flow and optical tweezers, as well as accurately reproducing bulk flow hallmarks of whole blood such as the Fåhraeus-Lindqvist effect and the CFL [31]. With this validated RBC model HemoCell has been used to study the effects of RBC cytoplasmic viscosity contrasts in bulk flow [32], the role of hematocrit profiles on cell diffusivities in flow [33], as well as identifying the start of a platelet aggregate [40]. The capabilities of HemoCell allow the tracking of the individual suspended healthy RBCs, stiffened RBCs, and platelets that are present in the in vitro experiments reported in this study.…”
Section: Stiffened Red Blood Cell Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, an increase in platelet flux of about two times in WB was found in comparison to PRP in Van Rooij’s flow chamber [van Rooij et al, submitted]. This increase is caused by enhanced diffusion due to the presence of red blood cells 32 . However, in PRP this enhanced diffusion is not present.…”
Section: Discussionmentioning
confidence: 84%